Are students’ ethical beliefs in an academic setting related to ethical decision-making in the workplace? - Ratu, Aurelius; Setyaningsih, Yuni; Rai, Ni Gusti Made; Rahmawati, Deti; Savitri, Eka Dian; Rahadiantino, Lienggar; Prasetyo, Banu (International Journal of Evaluation and Research in Education (IJERE), 2024)
When academic integrity is maintained not only in the framework of education but also in professionals’ lives, educational institutions have a moral commitment to generate graduates of high quality for the greater community. Graduates are expected to be both competent and ethical in their professional lives. This study builds on previous academic integrity research to delve into students’ ethical decision-making in real-world situations. During regular class time, undergraduate students from public and private universities in Surabaya, Indonesia, were surveyed (N=496). Using a two-sample t-test approach, the current study found students’ perceptions of their ethical perspective and situations in the workplace differed from their perceptions of themselves in current academic environment. This finding is worrisome because students who perceive themselves as lacking moral consistency believe that they have strong ethical convictions. Even though there was evidence to back up Lawson’s claim that the usefulness of an action is more essential than its ethicality, a workplace ethical decision reveals an anomaly in the operation of ethical decision-making. This study highlights the significance of cultivating risk-related decision-making throughout the educational process and should be encouraged as positive stimulant that prepares students for the ethical difficulties of the professional world.